Morpho-bathymetric acoustic surveys as a tool for mapping traces of anthropogenic activities on the seafloor: The case study of the Taranto area, southern Italy. (December 2022) - Rizzo, Angela; De Giosa, Francesco; Donadio, Carlo; Scardino, Giovanni; Scicchitano, Giovanni; Terracciano, Sabrina; Mastronuzzi, Giuseppe
Abstract: In this study, an investigation procedure for mapping the traces of anthropogenic activities on the seafloor is proposed. Analyses are based on the interpretation of acoustic data (Multibeam Echosounder and Side Scan Sonar) acquired in the Taranto coastal area. Specific GIS tools supported the acoustic data analysis, interpretation, and mapping. These analyses highlighted that the seafloor of both coastal basins included in the investigated area is affected by a high distribution of traces related to different anthropogenic activities such as dredging, shipping, and mussel farming activities. Such kind of traces resulted efficiently detectable from morpho-bathymetric acoustic data. In particular, groove traces resulted highly distributed in both basins, while sunken mussel farm facilities are widely distributed in the Mar Grande basin. The results highlight as acoustic surveys represent a useful tool for orienting effective coastal management actions. This study points out how geophysical surveys support the geo-environmental characterization of highly urbanized coastal sectors. Highlights: Mapping of anthropogenic traces on the seafloor from MBES and SSS data Up to 19 types of anthropogenic elements were identified from acoustic data. Mussel farms and grooves are among all the most numerous. Aerial photos and orthophotos used for change detection analysis 27 % and 78 % of disused area of mussel farms over the investigated period